Bowel Habits in Children - Sri Sulastri; M. Iqbal; Johnwan Usman; Atan Baas Sinuhaji; A. H. Sutanto (Paediatrica Indonesiana, 1995)
A cross sectional study of the bowel habits of 119 children (aged 2 years or less) was performed at PTP VIII, North Sumatera. The study was carried out on Desember 18 and 19, 1992, using questionnaire. Mean frequency of defecation was 1.2 times/day (± 0.49) and median volume of defecation was 25 mL/day. Out of 119 children, 9 children were on fluid diet, the mean frequency of defecation was 1.5 times/day (± 0.71) and the median volume of defecation was 5 mL/day. Eighty-eight children who were on fluid diet plus solid diet had a mean frequency of defecation 1.1 times/day (± 0.48) and median volume of defecation was 25 mL/day. Twenty two children who received solid diets had a mean frequency of defecation of 1.2 times/day (± 0.35) and median volume of defecation was 57.5 mL/day. The volume of defecation in children who received solid_diets was higher than children who bad not received solid diets (p < 0.05). There was a positive corelation between age and stool volume (r=0.4; p < 0.05).